Comparison of Next-Generation Assays for Fecal Calprotectin vs the PhiCal Assay. Issue 2 (14th August 2021) - Lin, Leo; Wyness, Sara P; Jensen, Ryan; Bird, Joseph; Norgyal, Tenzin; Jensen, Gabrielle; Johnson, Lisa M
Abstract: Objectives: To compare the PhiCal assay (CALPRO), the first US Food and Drug Administration–approved assay for fecal calprotectin, to 4 next-generation assays. Methods: Stool samples from 50 patients were selected, and relevant clinical information was collected. Comparisons were performed using the PhiCal, fCAL turbo (BÜHLMANN), LIAISON Calprotectin (DiaSorin), QUANTA Lite Calprotectin ELISA (Inova Diagnostics), and Calprotectin Chemiluminescence ELISA (ALPCO) assays. Results: All 4 assays had acceptable agreement with PhiCal when qualitatively categorizing results. Within the PhiCal reportable range of 16 to 1, 250 μg/g, the DiaSorin, Inova Diagnostics, and ALPCO assays had Spearman correlation coefficients of 0.98, 0.97, and 0.95 and positive biases of 17%, 20%, and 15%, respectively. The BÜHLMANN assay ran approximately 2-fold higher than the PhiCal assay but had a correlation coefficient of 0.98, with similar result categorization. Conclusions: Our results demonstrate good comparison between PhiCal and 4 next-generation assays. Laboratories performing fecal calprotectin assays may have compelling reasons to adopt next-generation fecal calprotectin testing, such as greater automation, a decreased number of replicates needed per test, and the use of stool-extraction devices. These benefits could decrease turnaround times and lower costs. Although the results of the assays correlated, they are not standardized. Laboratories adopting the newer assays will need to further investigate their performance through validation studies.